The impact of crying, sleeping, and eating problems in infants on childhood behavioral outcomes: A meta-analysis - Galling, Britta; Brauer, Hannah; Struck, Pia; Krogmann, Amanda; Gross-Hemmi, Mirja; Prehn-Kristensen, Alexander; Mudra, Susanne (Frontiers in Child and Adolescent Psychiatry, 2023)
Background There is increasing evidence that regulatory problems (RPs), such as excessive crying, sleeping or feeding problems in infancy, could be associated with the development of behavioral problems in childhood. In this meta-analysis we aimed to investigate the strength and characteristics of this association. Methods A systematic literature search (PubMed/PsycInfo, until 15/08/2021) for longitudinal prospective studies of infants with RPs and at least one follow-up assessment reporting incidence and/or severity of behavioral problems was conducted. The primary outcomes were (i) the cumulative incidence of behavioral problems in children (2–14 years) with previous RPs and (ii) the difference between children with/without previous RPs with regard to the incidence and severity of externalizing, internalizing and/or attention-deficit/hyperactivity disorder (ADHD) symptoms. Additionally, we analyzed behavioral problems of children with previous single, multiple or no RPs and with respect to age at follow-up. Subgroup and meta-regression analyses were added. Results 30 meta-analyzed studies reported on 34,582 participants (nRP = 5091, ncontrol = 29,491; age: baseline = 6.5 ± 4.5 months, follow-up = 5.5 ± 2.8 years) with excessive crying (studies = 13, n = 1577), sleeping problems (studies = 9, n = 2014), eating problems (studies = 3, n = 105), any single (studies = 2, n = 201) or multiple RPs (studies = 9, n = 1194). The cumulative incidence for behavioral problems during childhood was 23.3% in children with RPs. Behavioral problems were significantly more pronounced in infants with RPs compared to healthy controls (SMD = 0.381, 95% CI = 0.296–0.466, p < .001), particularly with multiple RPs (SMD = 0.291, p = 0.018). Conclusions Findings suggest that RPs in infancy are associated with overall behavioral problems (externalizing or internalizing behavior and ADHD symptoms) in childhood. Our data cannot explain linked developmental trajectories and underlying factors. However, detection of affected infants may help to adapt supportive measures to the individual familial needs to promote the parent-child-relationship and prevent the development of child behavioral problems from early on.